Descolonización y colonialismo interno: Lugar y función de lo colonial - Fernando Iturralde (Bolivian Studies Journal, 2016)
This article’s purpose is to find out what exactly is referred to by the term ‘colonial’ in three Bolivian intellectuals: René Zavaleta Mercado, Silvia Rivera Cusicanqui and H.C.F. Mansilla. In the writings of these three authors, I find elements that allow me to believe that they all have a similar (although     not the same) understanding of colonial heritage. In all three cases, that heritage is seen as something negative, i.e. something that should be put aside and ultimately abolished. On the basis of a textual analysis, I make the effort to understand exactly what this idea is about and what this remnant of colonial times consists of. Once I get to the point of understanding what the idea of the colonial signifies in each of these texts, I will analyze them applying mimetic theory given that this theory has concepts that are similar. In other words, I make an effort to translate the concepts of these three Bolivian intellectuals in terms of mimetic theory so as to better understand them, as well as to verify whether they have a meaning in the context of that theory. El siguiente artículo tiene como propósito indagar en la comprensión de aquello que es designado por el término “colonial” en tres intelectuales bolivianos: René Zavaleta Mercado, Silvia Rivera Cusicanqui y H.C.F. Mansilla. Encontramos, en los escritos de los tres, signos que nos permiten percibir una comprensión similar (aunque no la misma) de lo que entienden por herencia colonial. En los tres casos, esa herencia es vista de forma peyorativa, es decir, como un rasgo que habría que poner de lado y finalmente erradicar. A partir de un análisis textual tratamos de comprender en qué consiste ese concepto o ese remanente colonial en estos tres autores. Una vez que logramos averiguar a qué se podrían referir estos autores cuando manejan la idea de una herencia colonial, analizamos y cuestionamos estas ideas a partir de la concepción que la teoría mimética tiene de conceptos similares. En otras palabras, buscamos traducir los conceptos de los pensadores bolivianos en términos de la teoría mimética, ya sea para comprenderlos mejor, ya sea para verificar si tienen una significación en el contexto de esa teoría.